2022
DOI: 10.1590/0074-02760210385
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches towards the discovery and optimisation of cruzain inhibitors

Abstract: The need to develop safer and more efficacious drugs to treat Chagas disease has motivated the search for cruzain inhibitors. Cruzain is the recombinant, truncated version of cruzipain, a cysteine protease from Trypanosoma cruzi with important roles during the parasite life cycle. Several computational techniques have been applied to discover and optimise cruzain inhibitors, providing a molecular basis to guide this process. Here, we review some of the most recent computational studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It is possible to verify that its 8-methoxy-substituted coumarin nucleus is found at the S2 subpocket entry since it has a preference for van der Waals interactions with hydrophobic substituents, [74][75][76] while its thiosemicarbazone moiety is oriented toward the shallow S1 subpocket, which is typically associated with inhibitors and better accommodates non-bulky groups. 77,78 It may explain the better activity of FN-27 towards CRZ in our experimental assays. Additionally, it was observed that despite the nucleophilic Cys 25 residue being found near the methylamine double bond of FN-27 (a potential electrophilic moiety at a distance of 4.02 Å), it probably did not undergo covalent bonding, although an anion-p interaction could be possible for it.…”
Section: 5mentioning
confidence: 82%
“…It is possible to verify that its 8-methoxy-substituted coumarin nucleus is found at the S2 subpocket entry since it has a preference for van der Waals interactions with hydrophobic substituents, [74][75][76] while its thiosemicarbazone moiety is oriented toward the shallow S1 subpocket, which is typically associated with inhibitors and better accommodates non-bulky groups. 77,78 It may explain the better activity of FN-27 towards CRZ in our experimental assays. Additionally, it was observed that despite the nucleophilic Cys 25 residue being found near the methylamine double bond of FN-27 (a potential electrophilic moiety at a distance of 4.02 Å), it probably did not undergo covalent bonding, although an anion-p interaction could be possible for it.…”
Section: 5mentioning
confidence: 82%
“…Among the validated targets, cruzain, the main cysteine protease of T. cruzi, is one of the most well-studied. , Cruzain is relevant to the parasite life cycle, replication, immune response, and virulence and has been established as a validated target for trypanocidal compounds. Among the several compound classes reported as cruzain inhibitors, covalent inhibitors are especially interesting, given the overall potency and residence time provided by the covalent bond . The general mechanism of covalent inhibition of a protein by a small molecule (Figure ) starts with the formation of a reversible, low-affinity pre-covalent complex (E···I), which is governed by noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the validated targets, cruzain, the main cysteine protease of T. cruzi, is one of the most well-studied. 6,7 Cruzain is relevant to the parasite life cycle, replication, immune response, and virulence 8−10 and has been established as a validated target for trypanocidal compounds. 11−14 Among the several compound classes reported as cruzain inhibitors, 15−26 covalent inhibitors are especially interesting, given the overall potency and residence time provided by the covalent bond.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In particular, cruzain facilitates the invasion of host cells and modulates the immune response, allowing the parasite to establish an infection and proliferate within the host. [9] As cruzain passes through the endoplasmic reticulum and the Golgi apparatus, it is processed and modified, suggesting that this protease may be a useful marker to follow the transport and processing of proteins through the ER-Golgi-endosomal pathway in trypanosomatids. [10] Several inhibitors of CZ have been described, and some have shown efficacy against T. cruzi both in vitro and in animal models of infection.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Several inhibitors of CZ have been described, and some have shown efficacy against T. cruzi both in vitro and in animal models of infection. [8][9][10] These inhibitors act by blocking the autocatalytic processing and trafficking of cruzain in the Golgi complex of pimastigotes and amastigotes. [10] In addition, some of these compounds have been shown to be able to cure the infection in animal models, underscoring their potential as therapeutic agents against Chagas disease.…”
Section: Introductionmentioning
confidence: 99%